2021
DOI: 10.3233/jad-210720
|View full text |Cite
|
Sign up to set email alerts
|

Goals of Care Conversations and Subsequent Advance Care Planning Outcomes for People with Dementia

Abstract: Background: Advance care planning has been shown to improve end of life decision-making for people with dementia. However, the impact of goals of care conversations between people with dementia and their caregivers has not been characterized. Objective: In this study, we evaluate the association between goals of care conversations and advance care planning outcomes. Methods: Retrospective advance care planning measures were collected via a questionnaire administered to 166 caregivers after the death of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…The problem with this approach is that carepartner wishes may differ from those of the PWD. 14,35 Further, not all clinicians are equally equipped with the appropriate skillset to engage with and assess cognition in PWD. Hence the benefit of ACP in early-stage dementia, when communication ability is largely still preserved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The problem with this approach is that carepartner wishes may differ from those of the PWD. 14,35 Further, not all clinicians are equally equipped with the appropriate skillset to engage with and assess cognition in PWD. Hence the benefit of ACP in early-stage dementia, when communication ability is largely still preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Time constraints can be one reason why clinicians may default to carepartners in ACP 28,34 and overlook direct engagement with PWD. The problem with this approach is that carepartner wishes may differ from those of the PWD 14,35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACP provides patients and their care partners the opportunity to discuss their goals, values, and priorities for healthcare while also gaining a better understanding of their underlying serious illness and prognosis. [32][33][34] A recent scoping review and systematic review of high-quality ACP interventions have shown benefits regarding improving patient-physician communication, increasing patient-surrogate congruence in preferences, and decreasing anxiety, grief, posttraumatic stress, and burden for surrogate decision-makers; which are primary motivators for patients to engage in ACP. [35][36][37][38][39][40][41][42][43][44][45] Multiple barriers have been identified that hinder ACP discussions amongst PLWD and those with MCI.…”
Section: Introductionmentioning
confidence: 99%